2016
DOI: 10.1101/048595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation and evolution of the glutamine-rich repeat region of Drosophila Argonaute-2

Abstract: RNA interference pathways mediate biological processes through Argonaute-family proteins, which bind small RNAs as guides to silence complementary target nucleic acids . In insects and crustaceans Argonaute-2 silences viral nucleic acids, and therefore acts as a primary effector of innate antiviral immunity. Although the function of the major Argonaute-2 domains, which are conserved across most Argonautefamily proteins, are known, many invertebrate Argonaute-2 homologs contain a glutamine-rich repeat (GRR) reg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Indeed, in multiple invertebrate species the AGO2 gene (not phylogenetically related to plant AGO2 ) appears to have been subjected to high rates of adaptive protein evolution, including a highly variable N‐terminal glutamine‐rich repeat region (Palmer et al , ). However, strong evidence for a direct correlation between AGO2 polymorphisms and virus susceptibility has not been reported (Palmer & Obbard, ). Importantly, in our analysis, we found no polymorphisms in residues predicted to be important for small RNA loading and maturation, RNA binding, AGO hook or catalytic functions (Fátyol et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in multiple invertebrate species the AGO2 gene (not phylogenetically related to plant AGO2 ) appears to have been subjected to high rates of adaptive protein evolution, including a highly variable N‐terminal glutamine‐rich repeat region (Palmer et al , ). However, strong evidence for a direct correlation between AGO2 polymorphisms and virus susceptibility has not been reported (Palmer & Obbard, ). Importantly, in our analysis, we found no polymorphisms in residues predicted to be important for small RNA loading and maturation, RNA binding, AGO hook or catalytic functions (Fátyol et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The C‐terminal domain of SGTA, containing a glutamine‐rich region, is necessary for interaction with hydrophobic substrates (Liou and Wang, ). A glutamine‐rich repeat region has also been found in many invertebrate Argonaute‐2 (Ago2) homologs, which is a component of the RNA interference pathway (Palmer and Obbard, ). Although the role of this glutamine‐rich repeat is still unknown, it has been suggested that long poly‐glutamine‐rich regions facilitate protein adhesion and protein complex formation (Palmer and Obbard, ).…”
Section: Discussionmentioning
confidence: 99%
“…A glutamine‐rich repeat region has also been found in many invertebrate Argonaute‐2 (Ago2) homologs, which is a component of the RNA interference pathway (Palmer and Obbard, ). Although the role of this glutamine‐rich repeat is still unknown, it has been suggested that long poly‐glutamine‐rich regions facilitate protein adhesion and protein complex formation (Palmer and Obbard, ). Although GrtABC did not show high sequence similarities to SGTA and Ago2, which contain a glutamine‐rich region, it is possible that these proteins also interact with other proteins, resulting in a toxic effect on the growth of C. glutamicum .…”
Section: Discussionmentioning
confidence: 99%
“…Unique motifs that are exclusively present in particular species can be associated with several putative functions. For example, the presence of N-terminus motif 19 known as glutamine-rich repeat motifs (GRR) found exclusively in the EcR domain of D. magna is linked with potential antiviral immunity in crustaceans (Palmer & Obbard 2016). Among the N-terminus motifs, motif 12 encodes the phosphatidylinositol-specific phospholipase C (PI-PLC), a family of intracellular enzymes involved in signal transduction and biomineralisation processes (Rend on-Ram ırez et al 2013; Nam et al 2020).…”
Section: Evolutionary Relationships and Conservation Pattern Of Crustacean Ecrmentioning
confidence: 99%